The ceiling of the mandapa of the Kumbheshvar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
The ceiling of the mandapa (pillared hall) of the Kumbheshvar Mahadev temple. It is composed of concentric rings that form a dome. The inner circles of the ceiling are designed with floral cusps, and the outer rings have figural ornamentation. The ornamentation and details of the sculptures are partially lost because of the bat infestation on the stone fabric.